Vocabulary Easter eggs as a reflection of cultural and linguistic phenomenon of Ukrainians (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article provides an overview of different approaches to cultural and bulleted words, proposed to consider language as a cultural and Easter eggs labeled highlighted features of different language groups Easter eggs, displays the unique worldview of the Ukrainians.
Keywords: ethnolinguistics; vocabulary of Easter eggs; national and cultural component; in a civilized manner marking units